anonymous
  • anonymous
help! use the quadratic formula to solve x²+3=-4x
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
x^2+4x+3 = 0 (x+1) (x+ 3) = 0 then x = -1 or x = -3
anonymous
  • anonymous
no no use quadratic formula to solve @gerryliyana
anonymous
  • anonymous
do you know what the quadratic formula is? or are you asking for that.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i know what it is but i still dont know how 2 get the answer...
anonymous
  • anonymous
set up equation so that you have: ax^2+bx+c=0 and use a, b and c correctly in your formula
anonymous
  • anonymous
x²+4x+3=0?
anonymous
  • anonymous
so a=?,b=?, and c=?
anonymous
  • anonymous
yess ur all right
anonymous
  • anonymous
smart boy!!
anonymous
  • anonymous
a=o b=4 c=3
anonymous
  • anonymous
nooo
anonymous
  • anonymous
a = 1, b=4, c=3
anonymous
  • anonymous
yes
anonymous
  • anonymous
sorry i wasnt thinking
anonymous
  • anonymous
so now what?
anonymous
  • anonymous
use \[x = \frac{ -b \pm \sqrt{(b^{2} - 4ac)} }{ 2a }\]
anonymous
  • anonymous
substitute all parameter, including a, b, and c
anonymous
  • anonymous
to solve x²+4x + 3 =0 you should find the value of x, one way to do this by using formula above ...,
anonymous
  • anonymous
\[x = \frac{ -b \pm \sqrt{b^{2}-4ac} }{ 2a }\] \[x = \frac{ -4 \pm \sqrt{4^{2}-(4)(1)(3)} }{ 2(1) }\]
anonymous
  • anonymous
ok
anonymous
  • anonymous
Thanks both of you!

Looking for something else?

Not the answer you are looking for? Search for more explanations.